Obtaining a fused PLA‑calcium phosphate‑tobramycin‑based filament for 3D printing with potential antimicrobial application (2023)
ABSTRACT: Many eforts in the tissue engineering feld have been devoted to producing biomedical devices with several physico-chemical properties that could promote an increase in the quality of therapeutic treatments. Thus, 3D printing is an efcient method which facilitates manufacturing high quality products to be used as medical devices. However, high-performance materials are required for obtaining products that are able to be 3D printed to attend the biomedical concerns. In this work, fused PLA-calcium phosphate-tobramycin-based flaments with antimicrobial properties were produced. X-ray powder difraction, Fourier transform infrared spectroscopy and thermal analysis were performed to characterize the pure compounds as well as the composite flaments, revealing that the drug is preserved into the flaments by the implemented methodology, even after the hot extrusion procedure. The flaments and the printed pieces presented great antimicrobial efect and a controlledrelease profle was also observed by the drug-release assays for the flaments produced, thereby indicating this material as a promising candidate to be used for implantable medical devices in the future.